Comparison of machinability aluminium alloy LM6 when using coated and uncoated carbide cutting tool - Khuzaimi, Mohd Aris (2014)
The applications of metal matrix composites (MMCs) are being increasing daily in many field especially aerospace and automobile industries. The demand for affordable, quality materials and low costs also increased in line and led to the development of MMC as alternative product for various industrial application. The typical Aluminium Alloy LM6 contains 10-13 wt.% of silicon and thus inherently solidifies with coarse grain sizes. The main composition of LM6 is about 85.95% of pure Aluminium. Machining test for this material will be conducted by using two types of cutting tools which is coated carbide and uncoated carbide. It will be test at different cutting speed (i.e., 5000 rpm and 6000 rpm) and different feed (i.e., 90 mm/min and 120 mm/min) at constant depth of cut 0.5 mm. The difference between both cutting tools will be study in term of its tool wear behavior and also the surface integrity of materials as well. Machining test will use CNC Milling Haas machine with dry cutting condition. The results showed that tool life for cutting tool influences by coated carbide tool rather than uncoated carbide tool. Better surface roughness provides from coated carbide with 6000 rpm and feed rate 90 mm/min.